Pengembangan Media Pembelajaran Berbentuk Power Point Interaktif dalam Mata Pelajaran Pendidikan Agama Islam Kelas I SDN 1 Wringinanom - Anis Khusnul Inayah (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Learning media is one of the most important components in the learning process of an implementation. But in reality there are still a few teachers who still use the media in the learning process, thereby reducing student learning outcomes. One of the most frequently used learning media is power point media, interactive power point media is a medium that is easy and can be used by everyone and can be varied according to student needs. The aim is to describe the design and effectiveness of power point media in Islamic religious education subjects. This type of research is Research and Development using a 4D research model (Define, Design, Develop, Disseminate). Data analysis techniques using quantitative and qualitative through a questionnaire. The research subjects is 40% from students were 13 students of class 1 SDN Sukowinangun 2 Magetan. The data obtained is qualitative data and then converted into quantitative data by using product moment. The results showed that the developed media was declared valid with a percentage of two expert validators at 80% and from the results of student evaluations at 87%.